Effect of nano-ZnO with modified surface on properties of bitumen. (15th November 2015) - Li, Rui; Pei, Jianzhong; Sun, Changle
Highlights: Surface-modified inorganic nanoparticle nano-ZnO was developed. SMN-ZnO proved a good compatibility between surface-modified nano-ZnO and bitumens. The aging resistance of bitumen is improved obviously by SMN-ZnO. SMN-ZnOs could improvements in physical performance and aging resistance of bitumen. Abstract: The effects of surface-modified inorganic nanoparticle nano-ZnO on the physical and ultraviolet aging resistance of bitumen were investigated as well as the microstructures of the binders. The compatibility between inorganic nanoparticle nano-ZnO and bitumen was studied by high temperature stability test. Fourier transform infrared spectroscopy shows that surface-modified coupling agent has been introduced to the surface of nano-ZnO through chemical bond. The mass change rate and viscosity aging index of the bitumen are decreased by nano-ZnO after thin film oven test and pressure aging vessel aging. Surface-modified nano-ZnO more pronounced improvements in aging resistance of bitumen.